Innovative capacity and innovation systems and the economic development levels of European countries (Economic and Political Thought, 2015)
The paper aims to study the relationship between differences in nationalinnovation capabilities within three sectors, which are the main building blocksof an innovation system, and country variations in GDP per capita. Researchin this area has previously focused mostly on the impact of differently definedinnovation capabilities on the level of economic development of countries,neglecting innovation system sectors approach. The analysis conductedfor this paper has allowed do confirm that there is a positive relationshipbetween country variations in innovation capabilities within two of the sectors:enterprise sector and higher education sector, and national differences inGDP per capita. While the relationship between differences in innovationcapabilities within the latter sector is linear in character, the interdependencebetween country variations in enterprise sector innovation capabilities andeconomic development are evidently non-linear. Values of composite indexescalculated for the enterprise sector innovation capabilities above a certainlevel have not been accompanied by corresponding higher values of GDPper capita – this relationship has been evident in both analysed periods. Thestudy based on gathered statistical information has also allowed to concludethat during 10 years between 2002–2003 and 2012–2013 there have not beenobserved any significant changes on the Europe’s map of innovation leaders.